The transformation of Imbube music in Zimbabwe: a case of Bulawayo - Nleya, Martha (Midlands State University, 2014)
The research focuses on the transformation of ‘Imbube’ music in Zimbabwe. It interrogates the role and value of the transformation of ‘Imbube’ music in Bulawayo. The study is largely qualitative but it also employs some quantitative techniques. Similarly the study uses data collection methods such as structured and unstructured interviews, questionnaires, focus group discussions and document analysis in collecting data from ‘Imbube’ groups, audiences and academics. The Afrocentricity theory influences the arguments and analysis of this research. The study discovered that ‘Imbube’ music is ever changing due to changing times and its change is as a result to suit the taste of the new generation. As such the transformation of ‘Imbube’ music has been seen as a good idea by many as it meets the interests of the people. The study also establishes that the transformation of ‘Imbube’ music maintains some of the traditional values attached to it. However, the transformation has been largely influenced by mordenisation and it has led to the role of ‘Imbube’ music to be more of commercialisation. As such mordenisation has slowly assimilated traditional values of ‘Imbube’ music. This transformation of ‘Imbube’ music can be seen as a revolutionary shift in this genre of music. Therefore the study concludes that imbube is still transforming, and its transformation is highly recommended by the people as it suits the taste of the new generation.